TAM Pathways Explain Purchase Intention Satisfaction and Repurchase in Coffee Apps: Model TAM Menjelaskan Hubungan Antara Kepuasan dan Niat Membeli serta Pembelian Ulang pada Aplikasi Kopi - Putri, Zahra Khania; Waluyo, Minto (Academia Open, 2026)
General Background: Digital technology has become an important part of business operations and marketing, including in the food and beverage industry. Specific Background: Modern coffee shop applications are used to support transactions, service access, customer relationships, and digital consumer engagement. Knowledge Gap: Previous Technology Acceptance Model studies have mostly focused on technology adoption, while limited research extends TAM toward purchase intention, purchase decisions, purchase satisfaction, and repurchase behavior in coffee shop applications. Aims: This study aimed to analyze the relationships between application usage, application ease, application benefits, application risk, user trust, purchase intention, purchase decisions, purchase satisfaction, and repurchase. Results: Using a quantitative approach, questionnaire data from 160 respondents were analyzed through Structural Equation Modeling with AMOS. The modified model met acceptable goodness-of-fit criteria, with six indicators categorized as good and two as marginal. Application usage, application benefits, and user trust had significant relationships with purchase intention, while application ease and application risk were not significant. Purchase intention significantly related to purchase decisions, purchase decisions significantly related to purchase satisfaction, and purchase satisfaction significantly related to repurchase. Novelty: This study expands TAM by integrating consumer purchasing behavior variables into one structural model for coffee shop application users. Implications: The findings suggest that application managers should strengthen perceived benefits, active usage, trust, system speed, interface quality, service stability, and value-added features to support repurchase behavior. Highlights: App use, perceived value, and confidence were significant predictors. Ease and risk did not show significant relationships with buying interest. Satisfaction formed the final pathway toward repeat transactions. Keywords: TAM, Purchase Interest, Purchase Decision, Purchase Satisfaction, Repeat Purchase